2019
DOI: 10.1108/cc-08-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

Medical undergraduate students’ perception towards the use and non-use of e-books: a case from Pakistan

Abstract: Purpose The purpose of this study is to explore the perception of medical undergraduate students regarding their behavior towards use and non-use of e-books. It also elucidates their preferences between print and electronic book format. Design/methodology/approach It is a quantitative study based on survey method. A semi-structured questionnaire was used to collect the data from final year medical students of three medical colleges of Lahore, Pakistan. Statistical package for social sciences (SPSS) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…As Zeeshan et al (2020) identified that university students had familiarity with information literacy programmes, had skills to fulfil their information needs and also recognize their importance for academic achievements. Moreover, Rafiq and Warraich (2019) have identified barriers like distraction of different links on website, problems in finding relevant books and unfamiliarity about electronic books among medical students. The authors further suggested that librarians should be well aware about e-books and must create awareness among students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Zeeshan et al (2020) identified that university students had familiarity with information literacy programmes, had skills to fulfil their information needs and also recognize their importance for academic achievements. Moreover, Rafiq and Warraich (2019) have identified barriers like distraction of different links on website, problems in finding relevant books and unfamiliarity about electronic books among medical students. The authors further suggested that librarians should be well aware about e-books and must create awareness among students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have also used a similar technique (questionnaire survey) to measure the use, attitudes and perceptions of study participants about e-books. (Corlett-Rivera and Hackman, 2014; Abdullah and Gibb, 2008; Lamb, 2012; Posigha, 2012; Shelburn, 2009; Khan et al , 2016; Rafiq and Warraich, 2019). Powell and Connaway (2004) defined that “questionnaires are worthwhile data collection tool to collect the information from the large population in a short period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zohrabi (2013) remarked that researchers need to consider measuring reliability of their data either before or after collecting the data (p. 254). Literature also indicates that researchers devised questionnaires and checked the reliability after collecting the final data (Rafiq and Warraich, 2019;Rafiq et al, 2018;Warraich et al, 2018;Khan and Bhatti, 2012;Ahmed and Soroya, 2016). The reliability of the instrument for the present study was checked via Cronbach's alpha calculation after collecting final data.…”
Section: Quantitative Analysismentioning
confidence: 97%
“…Rafiq and Warraich [9] conducted a study on medical students e-book use in Pakistan, and it was found that the use and non-use of e-books are almost equal among students. Google books were preferred mostly and were used for academic purpose.…”
Section: Literature Reviewmentioning
confidence: 99%